B-cell immune repertoire sequencing in tobacco cigarette smoking, vaping, and chronic obstructive pulmonary disease in the COPDGene cohort - Moll, Matthew; Xu, Zhonghui; Boueiz, Adel; Ryu, Min Hyung; Silverman, Edwin K.; Cho, Michael H.; Hersh, Craig P.; Sauler, Maor; Polverino, Francesca; Kinney, Gregory L.; Curtis, Jeffrey L.; Crotty-Alexander, Laura E.; et al. (Frontiers in Immunology, 2025)
RationaleCigarette smoking (CS) impairs B-cell function and antibody production, increasing infection risk. The impact of e-cigarette use ('vaping') and combined CS and vaping ('dual-use') on B-cell activity is unclear.ObjectiveTo examine B-cell receptor sequencing (BCR-seq) profiles associated with CS, vaping, and dual-use.MethodsBCR-seq was performed on blood RNA samples from 234 participants in the COPDGene study. We assessed multivariable associations of B-cell function measures (immunoglobulin heavy chain (IGH) subclass expression and usage, class-switching, V allele usage, and clonal expansion) with CS, vaping, and dual-use. We adjusted for multiple comparisons using the Benjamini-Hochberg method, identifying significant associations at 5% FDR and suggestive associations at 10% FDR.ResultsAmong 234 non-Hispanic white (NHW) and African American (AA) participants, CS and dual-use were significantly positively associated with increased secretory IgA production, with dual-use showing the strongest associations. Dual-use was positively associated with class switching and B-cell clonal expansion, indicating increased B-cell activation, with similar trends in those only smoking or only vaping. The IGHV5-51*01 allele was increased in dual users.ConclusionsCS and vaping additively enhance B-cell activation, most notably in dual-users. CS and vaping are significantly associated to multiple alterations in B-cell function including increased class switching, clonal expansion, and a shift towards IgA-producing cell populations. These changes could be relevant to response to infection and vaccinations and merit further study.